PLEASE GIVE CORRECT ANSWERS WITH EXPLANATION ......
Attachments:
![](https://hi-static.z-dn.net/files/d90/abb96ad3e28640561550ebbbf77a6c25.jpg)
Answers
Answered by
1
Answer:
132
Step-by-step explanation:
substituting x =-6 in the given equation
Attachments:
![](https://hi-static.z-dn.net/files/dc4/1d6cd329e43224c9d6626e30cd337fb4.jpg)
Answered by
1
Answer:
p(x)=x³+3x²+4x+k
since x+6 is a factor then
zero of x+6is -6
now p(-6)= (-6)³+3(-6)²+4(-6)+k=0
=> -216+108-24+k=0
=> k= 132
Similar questions